1990
DOI: 10.1111/j.1440-1681.1990.tb01302.x
|View full text |Cite
|
Sign up to set email alerts
|

Naloxone‐induced Acth Release in Man Is Inhibited by Clonidine

Abstract: 1. Adrenergic mechanisms play an important role in regulation of ACTH release. We used the alpha 2-adrenergic agonist, clonidine, as a central nervous system inhibitor of ACTH release to see if it would alter naloxone-induced ACTH secretion in normal human volunteers. 2. There was a significant blunting of the mean peak level of ACTH and the mean peak change of ACTH from basal as well as the area under the ACTH-time curve when clonidine was given prior to naloxone. 3. We conclude that clonidine, by blocking ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…In the monkey, we have previously demonstrated that inhibitory effects of CRH and of vasopressin on pulsatile LH release occur through the activation of endogenous opiate peptides since both effects are prevented by naloxone infusion [20,40]. That the cortisol increase following LPS persists in the presence of naloxone may not be surprising, since naloxone itself is known to stimulate the HPA axis in several species [41][42][43].…”
Section: Discussionmentioning
confidence: 98%
“…In the monkey, we have previously demonstrated that inhibitory effects of CRH and of vasopressin on pulsatile LH release occur through the activation of endogenous opiate peptides since both effects are prevented by naloxone infusion [20,40]. That the cortisol increase following LPS persists in the presence of naloxone may not be surprising, since naloxone itself is known to stimulate the HPA axis in several species [41][42][43].…”
Section: Discussionmentioning
confidence: 98%
“…Decreases in cortisol levels during placebo administration could be a consequence of pain relief or part of the endogenous opioid modulation of the hypothalamicpituitary-adrenal axis. Hypothalamic corticotrophin-releasing hormone neurons receive direct inhibitory input from b-endorphin producing neurons in the arcuate nucleus, but also regulate corticotrophin-releasing hormone neurons indirectly through noradrenergic mechanisms (Jackson et al, 1990). Naloxone, a non-selective opioid receptor antagonist, induces increases in adrenocorticotropic hormone and cortisol levels, an effect thought to be mediated through the blockade of b-endorphin and enkephalinergic input to corticotrophin-releasing hormone neurons (Bujdoso et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The hypothalamic CRH neurons receive direct inhibitory input from b-endorphin-producing neurons located in the arcuate nucleus. In addition, b-endorphinproducing neurons inhibit norepinephrine neurons, which provide direct stimulatory input to hypothalamic CRH neurons (Jackson et al, 1990). One could posit that compared with individuals expressing only the A allele, persons expressing the G allele (and hence a higher-affinity MOR) have higher inhibitory opioidergic tone directed at CRH neurons.…”
Section: Discussionmentioning
confidence: 99%